Running Parameter Sweep applications on Everest cloud platform - S. Yu. Volkov; O. V. Sukhoroslov (Компьютерные исследования и моделирование, 2015)
Parameter sweep applications are a very important class of applications, which are typically defined as a set of computational experiments over a set of input parameters, each of which is executed with its own parameter combination. These computations arise in many scientific contexts. This article introduces the Parameter Sweep web service that runs such applications in distributed computing environment. Also discussed is the Everest cloud platform, on which this service is built.